The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00420-011-0675-y
|View full text |Cite
|
Sign up to set email alerts
|

Moral issues in workplace health promotion

Abstract: PurposeThere is debate to what extent employers are entitled to interfere with the lifestyle and health of their workers. In this context, little information is available on the opinion of employees. Within the framework of a workplace health promotion (WHP) program, moral considerations among workers were investigated.MethodsEmployees from five companies were invited to participate in a WHP program. Both participants (n = 513) and non-participants (n = 205) in the program filled in a questionnaire on individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 15 publications
3
44
0
Order By: Relevance
“…This is due to the continuous escalation of care costs and the prioritisation of co-worker health by businesses (Sparling, 2010). Also, in public health policy in most western countries, health promotion is a cornerstone (Robroek, van de Vathorst, & Burdorf, 2012). During the last few decades, management concepts such as Lean Production, Total Quality Management (TQM), Business Process Reengineering and Integral Health Management have been used to promote changes and development towards business excellence (see, for instance, Docherty, 2002;Zwetsloot & Pot, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the continuous escalation of care costs and the prioritisation of co-worker health by businesses (Sparling, 2010). Also, in public health policy in most western countries, health promotion is a cornerstone (Robroek, van de Vathorst, & Burdorf, 2012). During the last few decades, management concepts such as Lean Production, Total Quality Management (TQM), Business Process Reengineering and Integral Health Management have been used to promote changes and development towards business excellence (see, for instance, Docherty, 2002;Zwetsloot & Pot, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Another reason for lower participation among employees with lower self-rated health could be less healthy employees’ desire to keep their private life and their work life separate. One study found indications that employees with unhealthy lifestyles or who are in poor health are more likely to resist employer interference with employee health [42]. Lower participation among employees with negative self-rated health has been reported in an earlier study on this HRA [41] and other WHPPs [14], but these reports are not consistent [43].…”
Section: Discussionmentioning
confidence: 93%
“…Following on this is the second possible underlying cause for small effects in general, which is the lack of awareness about the ethical side of WHP. Employees can experience WHP interventions as interference in their privacy, which in its turn can a play role in employees' decision whether to or not to participate [20]. On the other hand, as employees depend on their employer to maintain their job, employees might feel coerced to participate in WHP interventions [16].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as employees depend on their employer to maintain their job, employees might feel coerced to participate in WHP interventions [16]. Also, questions such as how far an employer can go in promoting employees' health often rises [20] as well as whether (and to what extent) employees are responsible for their health or whether their employer is [19]. To conclude, it is important to take into account the ethical questions and the conflicting values that come along with WHP, as they can influence participation in WHP and the relationships at the workplace.…”
Section: Introductionmentioning
confidence: 99%